Development of a whey protein beverage - Hammerby, Josefine (2015)
The aim of the study was to develop a whey protein base beverage for a specific target group, Baby boomers. The Baby boomers are the generation born between 1946-1964. Consumer research shows that this group takes a keen interest in their health and have the ambition to stay healthy. However, at the same time age related conditions, like stiff joints but also cancer, starts to appear. Therefore a product based on whey protein, with health benefits suitable for this target group was developed. The product was developed in coop-eration with Arla Foods; the product development process was hence according to their routines. Background information about the needs of Baby boomers, requirements of the product, process and ingredients was gathered through literature research and interviews with employees at Arla Foods Three powders with different whey protein content were tested in a raspberry flavoured beverage Vitamin D and calcium was included in the recipe to add health benefits. Samples were produced in lab scale, but also in a pilot plant. Some problems with the process occurred in the first pilot plant trial and several changes had to be made in the second trial. A trained sensory panel then evaluated the samples, and nutri-tional values were calculated. The sensory evaluation showed all the three samples had off flavours, and one sample also separated when raspberry puree was added. The nutritional value was calculated based on the recipes. The values differed between the samples, with better results for the whey protein powders with higher protein content. More work has to be done to improve the nutritional values, but most of all the sensory properties of the product.